Peranan Lingkungan Sekolah dan Kemampuan Berkomunikasi Guru Terhadap Motivasi Belajar Siswa - Darmawan, Didit; Issalillah, Fayola; Retnowati, Eli; Mataputun, Donny Richard (Universitas Nusantara PGRI Kediri, 2021)
This study aims to analyze and determine the effect of the school environment and teacher's communication skills on students' learning motivation. The sample in this study was 120 respondents who were taken purposively. The students who were used as respondents were third grade students. The analysis tool is multiple linear regression. The findings obtained are the school environment and the teacher's communication skills have a significant influence partially and simultaneously on students' learning motivation. The school environment has the most dominant influence on students' learning motivation.